1996
DOI: 10.1203/00006450-199606000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Serine and Glycine Metabolism in Hepatocytes from Mid Gestation Fetal Lambs

Abstract: Using stable isotopes of serine, glycine, and glutamine, the metabolism of serine and glycine was investigated in primary hepatocytes from six mid-gestation fetal lambs (mean gestational age = 81 +/- 6 d, normal gestation = 145 d). Serine production was 6.84 +/- 1.22 mumol/24 h/mg of DNA and exceeded serine utilization (3.76 +/- 1.44 mumol/24 h/mg of DNA) with a resultant net increase in medium serine of 2.58 +/- 1.70 mumol/24 h/mg of DNA. In contrast, glycine production (6.84 +/- 1.16 mumol/24 h/mg of DNA) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…In liver, the non-phosphorylated pathway is presumed to operate mainly in the reverse direction for gluconeogenesis (4). Glycine also can be converted directly into L-serine by serine hydroxymethyltransferase, with N 5 ,N 10 -methylenetetrahydrofolate acting as a carbon donor (5). The relative contribution of these pathways to L-serine biosynthesis in vivo, however, remains to be determined.…”
mentioning
confidence: 99%
“…In liver, the non-phosphorylated pathway is presumed to operate mainly in the reverse direction for gluconeogenesis (4). Glycine also can be converted directly into L-serine by serine hydroxymethyltransferase, with N 5 ,N 10 -methylenetetrahydrofolate acting as a carbon donor (5). The relative contribution of these pathways to L-serine biosynthesis in vivo, however, remains to be determined.…”
mentioning
confidence: 99%
“…glycine at approximately 10% enrichment for a further 24 h. Media was harvested at 0 and 24 h, cellular debris was removed by centrifugation, and the media was snap-frozen on dry ice and stored at Ϫ80°C until analysis. Serine and glycine 13 C media mole percent enrichment and concentration were determined at 0 and 24 h by GC/MS (11,12). Serine and glycine interconversion, production, and utilization rates were determined by stable isotope dilution as we have previously described (11,12).…”
Section: Methodsmentioning
confidence: 99%
“…It is now clear that fetal hepatic serine synthesis is not dependent on the ontogeny of the key enzymes of serine metabolism (Fig. 1) (13) or substrate availability (11,14).Serine and folate metabolism are directly linked. Studies in neuroblastoma cells that over-express MTHFS found a significant increase in serine production (15).…”
mentioning
confidence: 99%
“…Others and we have demonstrated that the majority of serine produced by the fetal liver is derived from glycine (2,11,12). However, the regulation of fetal hepatic serine metabolism is unclear.…”
mentioning
confidence: 99%
“…It is now clear that fetal hepatic serine synthesis is not dependent on the ontogeny of the key enzymes of serine metabolism (Fig. 1) (13) or substrate availability (11,14).…”
mentioning
confidence: 99%